The Determinants of Investment Behavior of Saudi Industrial Firms - Hechmi, Soumaya Bechir (International Journal of Economics and Financial Issues, 2020)
In this paper, we examine simultaneous relationship between respectively cash flow, dividend yield, debt, firm size and the investment. This research used 51 listed Saudi industrial firms, from 2009-2018. First of all, we have noticed that the CF has a statistically significant and positive effect on investment. Second, the dividend yield rate is negatively correlated with the investment. Third, debt and the firm size have a positive and significant effect on the relationship between investment and cash flow. This finding is not a sign of presence of financial constraints but it means that firms of our sample substitute the distribution of dividends by debts. Keywords: investment behavior, investment-cash flow sensitivity, dividend distribution, debt, firm size and financial constraints. JEL Classifications: G31, G32, O16, P330 DOI: https://doi.org/10.32479/ijefi.9233